DOUBLE-BURDENED AND MARGINALIZED WOMEN: Patriarchal Dominance in the Development in Padang Lawas, North Sumatera - Pohan, Muslim (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
Village Law Number 6 of 2014 stipulates the principles of participation, equality, and empowerment to make women subordinate in village development. This discourse cannot be separated from the role of the Batak Angkola Padang Lawas community, which is deeply committed to the patriarchal system. Women who work in development must face this well-established wall of old social construction. The study intends to investigate the reasons why women are marginalized in this development agenda. The data was gathered through documentation and interviews. Based on the patriarchal theory of Walby, it is safe to say that the construction of women's positions in village development in Padang Lawas is a manifestation of constructed patriarchal culture, which has long been part of Batak culture. Women's